Group Portrait in March 1916 [see ua-pho_00000703] (1916)
[see ua-pho_00000703] Standing: Arthur Matthews, Helen Shippey, Grace Sims, Dan Riley, [Zilbah Torbes], Marcella Fitz, Perry Martinsen; 1st row sitting: Jack Leonard, Peggy Shippey; 2nd row sitting: Jerry Fitzgerald, Bernice Dempsey, Jean Riley, Howard Sebastian, Ellen Hughes; 3rd row sitting: Mick Gates, Lena Janssen, Eva Tuley, John Fitzgerald; 4th row sitting: Josie Renetzky, John Brown, Happy Mitchell, Maurice Cheda? March 1916